2019
DOI: 10.1002/kjm2.12091
|View full text |Cite
|
Sign up to set email alerts
|

Increased miR‐323a induces bladder cancer cell apoptosis by suppressing c‐Met

Abstract: The current study aimed to evaluate the expression and role of miR‐323a in the progression of bladder cancer (BC), thereby providing a theoretical basis and potential therapy methods for BC patients. Our data showed that miR‐323a levels were significantly reduced in BC tissues compared with those of non‐cancerous tissues. Meanwhile, miR‐323a was significantly decreased in human BC cell lines (T24, J82, TCCSUP, RT‐112) than that in human normal bladder epithelial cell line SV‐HUC‐1. Furthermore, inhibition of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…24 Also, in bladder cancer, miR-323a overexpression elicits tumor cell apoptosis through targeting c-Met. 25 In this study, miR-323a showed to be downregulated within pancreatic cancer tissue samples and cells based on online datasets and experimental analyses, suggesting its potential role in suppressing pancreatic cancer. Indeed, miR-323a overexpression significantly suppressed pancreatic carcinoma cell proliferation and colony formation.…”
Section: Discussionmentioning
confidence: 64%
“…24 Also, in bladder cancer, miR-323a overexpression elicits tumor cell apoptosis through targeting c-Met. 25 In this study, miR-323a showed to be downregulated within pancreatic cancer tissue samples and cells based on online datasets and experimental analyses, suggesting its potential role in suppressing pancreatic cancer. Indeed, miR-323a overexpression significantly suppressed pancreatic carcinoma cell proliferation and colony formation.…”
Section: Discussionmentioning
confidence: 64%
“…There were significant miR-323a downregulations in BCa tissues and cell lines. MiR-323a induced apoptosis of BCa cells through c-MET inhibition [99]. MiR-409-3p downregulation was also observed in BCa tissues and cell lines.…”
Section: Class V Vii and Viii Receptors Of Tyrosine Kinasesmentioning
confidence: 86%
“…A large number of studies have shown that miRNAs regulate more than one-third of all human genes in a sequence-specific manner [27][28][29][30]. Aberrant regulation of miRNAs functionally promotes the occurrence and development of different human cancers by regulating the degradation or translation of mRNAs [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%